Evaluation of the Implementation of Traditional Market Health Protocols in East Java - Sri Roekminiati; Ika Devy Pramudiana; Ananda Octavian Sasqia Putri; Anggi Mahdalena; Semuel Risal (PT FORMOSA CENDEKIA GLOBAL, 2023)
The occurrence of the Second Wave of the Covid-19 Pandemic has made the Indonesian government issued a new policy called the Emergency PPKM Policy with Health Protocols (Prokes). A policy must have an impact on people's lives, as well as scrap metal traders at Setono Betek Market in Kediri City and PKL Culinary Center and traditional market in Rungkut District, Surabaya City. This research was conducted with the aim of knowing how the impact of PPKM Darurat in the control of health protocols on the lives of iron traders who had to close their stalls for two weeks according to applicable regulations and controlling prokes by Satpol PP at the PKL at the Culinary Center in Rungkut District, Surabaya City. This type of research is descriptive research with a qualitative approach. With data collection methods through interviews, documentation, field studies, and literature studies. Technical Data analysis in this study uses interactive methods through data reduction, data presentation, and conclusion drawing. The results of this study show that the Emergency PPKM regulation makes these iron traders must close their stalls for two weeks, namely in the initial period of July 3-July 20, 2021. As a result of this closure, scrap metal traders experienced a decrease in an average turnover of almost 90%. The social impact these iron merchants feel is also complex, especially on behavior change. An appeal to do marketing online, but still, not all merchants can take advantage of existing technology. While the control of the health process by Satpol PP, Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy